RNA Sequencing of Human Peripheral Blood Cells Indicates Upregulation of Immune-Related Genes in Huntington's Disease - Andrade-Navarro, Miguel A.; Mühlenberg, Katja; Spruth, Eike J.; Mah, Nancy; González-López, Adrián; Andreani, Tommaso; Russ, Jenny; Huska, Matthew R.; Muro, Enrique M.; Fontaine, Jean-Fred; Amstislavskiy, Vyacheslav; Soldatov, Alexei; et al. (Frontiers in Neurology, 2020)
Huntington’s disease (HD) is an autosomal dominantly inherited neurodegenerative disorder caused by a trinucleotide repeat expansion in the Huntingtin gene. As disease-modifying therapies for HD are being developed, peripheral blood cells may be used to indicate disease progression and to monitor treatment response. In order to investigate whether gene expression changes can be found in the blood of individuals with HD that distinguish them from healthy controls, we performed transcriptome analysis by next-generation sequencing (RNA-seq). We detected a gene expression signature consistent with dysregulation of immune-related functions and inflammatory response in peripheral blood from HD cases versus controls, including induction of the interferon response genes, IFITM3, IFI6 and IRF7. Our results suggest that it is possible to detect gene expression changes in blood samples from individuals with HD, which may reflect the immune pathology associated with the disease.